2016
DOI: 10.1080/14992027.2016.1261189
|View full text |Cite
|
Sign up to set email alerts
|

Going wireless and booth-less for hearing testing in industry

Abstract: Objective To assess the test-retest variability of hearing thresholds obtained with an innovative, mobile wireless automated hearing-test system (WAHTS) with enhanced sound attenuation to test industrial workers at a worksite as compared to standardized automated hearing thresholds obtained in a mobile trailer sound booth. Design A within-subject repeated-measures design was used to compare air-conducted threshold tests (500 to 8000 Hz) measured with the WAHTS in six workplace locations, and a third test usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 27 publications
2
60
0
Order By: Relevance
“…A review of the literature revealed that there are three ways to implement automated audiometry. These are software solutions [ 2 7 8 9 10 11 12 ], hardware solutions [ 13 14 15 ], and smartphone/tablet solutions [ 3 5 16 17 18 19 ]. Each of these solutions is discussed below.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A review of the literature revealed that there are three ways to implement automated audiometry. These are software solutions [ 2 7 8 9 10 11 12 ], hardware solutions [ 13 14 15 ], and smartphone/tablet solutions [ 3 5 16 17 18 19 ]. Each of these solutions is discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…In a number of studies, hardware solutions have been proposed to be used in automated audiometry. According to the literature, the KUDUwave portable audiometer [ 13 14 15 ] and an earphone designed to remove environmental noise [ 16 ] were among the hardware solutions proposed for performing automated audiometry. The KUDUwave is a portable audiometer that makes real-time audiogram recording possible.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations